The Brokenwood mysteries. Series 11 [videorecording (DVD)]. - Rea, Neill, 1971-; Sutherland, Fern; Rawiri, Jarod (Acorn, 2025)
From seemingly supernatural incidents in the idyllic community of Brokenwood to mysterious murders with hidden motives, Shepherd and his team plunge into a web of deception, greed, and dark secrets as they tackle their most perplexing cases yet.